The Effect of Student Team Achievement Divison (STAD) Learning Model on Students’ Reading Comprehension t Mts Asrorul Huda Bekasi - Jamil, Ayu Rahmi Kintan; E, Yon A.; Edi, Syamsi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Reading comprehension is an essential skill in English learning, yet many Indonesian students face difficulties due to limited vocabulary and low motivation. This study aims to examine the effect of the Student Team Achievement Division (STAD) learning model on students’ reading comprehension. Using a quasi-experimental design with one-group pre-test and post-test, the study involved 13 seventh-grade students of MTs Asrorul Huda Bekasi in the academic year 2024/2025. Data were collected through essay-type reading comprehension tests and analyzed using paired sample t-test with SPSS 27. The findings showed that students’ mean scores improved from 56.46 (pre-test) to 69.38 (post-test). The t-test result (t = -9.562, p < 0.05) confirmed the significant effect of STAD in enhancing reading comprehension. The study highlights the importance of cooperative learning in fostering active participation and better comprehension outcomes.